Assessment of School-Based Sexual and Reproductive Health Education in Secondary Schools in Klang Valley, Malaysia - Kamrani, Mahnaz Akbari (2011)
The general purpose of this study was to assess school-based sexual and reproductive health education among female secondary school students.Subsequently the study examined the perspective of Science teachers and their views on school-based sexual and reproductive health education, as well as sex education in the current curriculum. This research had been designed with multiple studies conducted using a mixed methods approach. In phase I of the quantitative study, 520 female students were selected for this cross-sectional study by using a two-stage stratified random sampling. In all, 10 secondary schools were randomly selected as study sites from a total of 276.Subsequently, in phase II; a generic qualitative data gathering was conducted. The participants were science teachers selected by purposeful sampling from selected government secondary schools in phase I. Data were also harvested from semi-structured interviews with science teachers, and a contextual textbook analysis. The findings, in regards to the female student’s knowledge about sexual and reproductive health, revealed that the level of total knowledge was moderate. Additionally, the findings of this study revealed that female students were only moderately aware about issues regarding puberty and condom use. The conclusion drawn from the student participants suggested that a majority of respondents fell into the moderate sexual attitude category which clearly indicates that the surveyed subjects were “uncertain” about their attitudes towards sexual matters. Besides, the findings from this study clearly demonstrated that specially trained teachers are necessary for delivering this course. The results of the current study were in line with literature which found that most of the teachers for this subject did not receive any special training. On the other hand, regarding the constraints of the current school-based sexual and reproductive health education program, the majority of participants named teaching strategy and capacity of teachers, the lack of co-operation from the school and parents, limited resources in teaching and students themselves as some of the challenges. Thus, before a school-based health program can be introduced into the classrooms, the training of specialized teachers becomes a key consideration.